The Increased Expressions of Type IV Collagen in Cochlear Fibroblasts of Diabetic Rat Models Caused by Curcumin Therapy - Tengku Siti Hajar Haryuna, Farhat Farhat, Faathir Agung Ainul Taufika, Juliandi Harahap, Lidya Imelda Laksmi, Wayan Suardana (Journal of Applied Pharmaceutical Science, 2017)
Damage to fibroblasts within the cochlear lateral wall is suggested as one of the causes of hearing loss in patients with diabetes mellitus. The aim of this study was to prove curcumin as a safe and effective substance to treat the cochlear fibroblasts damage measured by the expressions of type IV collagen. Twenty-four Rattus norvegicus were randomly divided into 6 groups (n=4). Group I: the control group; group II: the diabetic group; group III and IV: the diabetic groups received curcumin therapy 200 and 400 mg/kgBW/day from day 3 - 5; group V and VI: the diabetic groups received curcumin therapy 200 and 400 mg/kgBW/day from day 3 - 10. Curcumin [16.62 ± 0.14]% w/w compared to Standard was administered orally, derived from Curcuma longa Linnaeus (turmeric). All samples were immunohistochemistrically examined for the expressions of type IV collagen in cochlear fibroblasts. Statistically significant differences were found for the expressions of type IV collagen (p
Keywords: Diabetes mellitus, curcumin, type IV collagen, fibroblast, cochlea.